The relationship between two different measures of osteoarthritis bone pathology, bone marrow lesions and 3D bone shape: data from the Osteoarthritis Initiative. Issue 10 (October 2018) - Dube, B.; Bowes, M.A.; Hensor, E.M.A.; Barr, A.; Kingsbury, S.R.; Conaghan, P.G.
Summary: Objective: Bone shape and bone marrow lesions (BMLs) represent different features of Magnetic resonance imaging (MRI)-detected subchondral pathology in osteoarthritis (OA). The aim of this study was to determine how these features are related and how they change in OA progression. Methods: 600 participants from the Osteoarthritis Initiative (OAI) FNIH Biomarkers Initiative were included, having Kellgren–Lawrence grade 1–3, at baseline and MRI data at baseline and 24 months. The associations between 3D quantitative bone shape vectors and presence of (MRI Osteoarthritis Knee Score) MOAKS semi-quantitative BMLs (total BML size ≥1) were analysed for femurs and tibias using linear regression. Responsiveness over 24 months was calculated for both features in four pre-defined progression groups and reported as standardised response means (SRMs). Multilevel models investigated the longitudinal relationship between change in BML size and change in bone shape. Results: Mean age was 61.5, 59% female and mean body mass index (BMI) 30.7. Correlation between baseline femur vector and BML was r  = 0.28, P  < 0.001. The presence of BMLs was associated with higher bone shape vector; coefficient (95% CI) 0.75 (0.54, 0.96) and 0.57 (0.38, 0.77) for femur and tibia respectively, both P  < 0.001. After covariate adjustment, only the femur remained significant [coefficient 0.49, (95% CI 0.30, 0.68)]. Longitudinally bone vector demonstrated more responsiveness to change than BMLs (SRM 0.89 vs 0.13) while multilevel models revealed that increase in BML size was related to a more positive bone shape vector (representing worsening OA). Conclusion: There is a relationship between bone shape and BMLs, with prevalence of BMLs associated with increasing OA bone shape. Bone shape demonstrated greater responsiveness than semi-quantitative BMLs.